2019
DOI: 10.1002/jcop.22229
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effect of perceived social support on the relationship between mindfulness and burnout in special education teachers

Abstract: This study aimed to explore the mediating effect of perceived social support on the relationship between mindfulness and burnout in Chinese special education teachers. Three hundred and seven teachers completed the Five‐Facet Mindfulness Questionnaire, Multi‐dimensional Scale of Perceived Social Support Scale, and Teacher Burnout Inventory. The results showed that burnout was negatively correlated with mindfulness and perceived social support, while perceived social support was positively correlated with mindf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…A few cross-sectional studies have demonstrated that dispositional mindfulness was associated with social support in teachers (Sun et al, 2019) and college students (Kuhl & Boyraz, 2017; Swickert et al, 2019), but none of these studies tested possible mediators between the two concepts. During a crisis when social interactions and resources are scarce, the perceptions of social connectedness and support for parents necessitate cognitive and emotional processes, such as acceptance of feelings and thoughts, focused attention, and skills in regulating negative emotions via awareness, clarity, acceptance, intention, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few cross-sectional studies have demonstrated that dispositional mindfulness was associated with social support in teachers (Sun et al, 2019) and college students (Kuhl & Boyraz, 2017; Swickert et al, 2019), but none of these studies tested possible mediators between the two concepts. During a crisis when social interactions and resources are scarce, the perceptions of social connectedness and support for parents necessitate cognitive and emotional processes, such as acceptance of feelings and thoughts, focused attention, and skills in regulating negative emotions via awareness, clarity, acceptance, intention, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Data has shown that mindfulness was associated with perceived social connection through effective emotion regulation in social contexts (Quaglia et al, 2015), which suggests a possible direct link between MER and perceived social support. Other studies measured dispositional mindfulness and found that it was concurrently associated with perceived social support (Sun et al, 2019; Swickert et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of such research deserves our attention. And, several studies have confirmed that mindfulness can make people more positively predict perceived social support (Kuhl and Boyraz, 2017;Sun et al, 2019). This may be because mindfulness enables individuals to focus on their current experience and realize the support they receive from social networks.…”
Section: The Effect Of Social Support On State Anxiety During the Epimentioning
confidence: 94%
“…Besides, it has been proven that the teachers are exhausted and stressed out when they have to teach children with disorders such as motor skills, social behavior issues, and intellectually disabled children as compared to the regular children due to the challenges faced ( Jovanović et al, 2019 ). Another study reported that the increasing levels of teacher burnout in special schools is linked to the challenging behaviors exhibited by the special children ( Sun et al, 2019 ; Din et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%